Effective interprofessional simulation training for medical and midwifery students. (5th October 2015) - Edwards, S E; Platt, S; Lenguerrand, E; Winter, C; Mears, J; Davis, S; Lucas, G; Hotton, E; Fox, R; Draycott, T; Siassakos, D
Abstract : Introduction: Good interprofessional teamworking is essential for high quality, efficient and safe clinical care. Undergraduate interprofessional training has been advocated for many years to improve interprofessional working. However, few successful initiatives have been reported and even fewer have formally assessed their educational impact. Methods: This was a prospective observational study of medical and midwifery students at a tertiary-level maternity unit. An interprofessional training module was developed and delivered by a multiprofessional faculty to medical and midwifery students, including short lectures, team-building exercises and practical simulation-based training for one obstetric (shoulder dystocia) and three generic emergencies (sepsis, haemorrhage, collapse). Outcome measures were interprofessional attitudes, assessed with a validated questionnaire (UWE Interprofessional Questionnaire) and clinical knowledge, measured with validated multiple-choice questions. Results: Seventy-two students participated (34 medical, 38 midwifery). Following training median interprofessional attitude scores improved in all domains (p<0.0001), and more students responded in positive categories for communication and teamwork (69–89%, p=0.004), interprofessional interaction (3–16%, p=0.012) and interprofessional relationships (74–89%, p=0.006). Scores for knowledge improved following training for medical students (65.5% (61.8–70%) to 82.3% (79.1–84.5%) (median (IQR)) p<0.0001) and student midwives (70% (64.1–76.4%) to 81.8% (79.1–86.4%) p<0.0001), and in all subject areas (p<0.0001). Conclusions: This training was associated with meaningful improvements in students' attitudes to teamwork, and knowledge acquisition. Integrating practical tasks and teamwork training, in authentic clinical settings, with matched numbers of medical and non-medical students can facilitate learning of both why and how to work together. This type of training could be adopted widely in undergraduate healthcare education.